Drivers of Atmosphere-Ocean CO2 Flux in Northern Norwegian Fjords - Aalto, Nerea J.; Campbell, Karley; Eilertsen, Hans C.; Bernstein, Hans C. (Frontiers in Marine Science, 2021)
High-latitude fjords and continental shelves are shown to be sinks for atmospheric CO2, yet large spatial-temporal variability and poor regional coverage of sea-air CO2 flux data, especially from fjord systems, makes it difficult to scale our knowledge on how they contribute to atmospheric carbon regulation. The magnitude and seasonal variability of atmosphere-sea CO2 flux was investigated in high-latitude northern Norwegian coastal areas over 2018 and 2019, including four fjords and one coastal bay. The aim was to assess the physical and biogeochemical factors controlling CO2 flux and partial pressure of CO2 in surface water via correlation to physical oceanographic and biological measurements. The results show that the study region acts as an overall atmospheric CO2 sink throughout the year, largely due to the strong undersaturation of CO2 relative to atmospheric concentrations. Wind speed exerted the strongest influence on the instantaneous rate of sea-air CO2 exchange, while exhibiting high variability. We concluded that the northernmost fjords (Altafjord and Porsangerfjord) showed stronger potential for instantaneous CO2 uptake due to higher wind speeds. We also found that fixation of CO2 was likely a significant factor controlling pCO2 from April to June, which followed phenology of spring phytoplankton blooms at each location. Decreased pCO2 and the resulting sea-air CO2 flux was observed in autumn due to a combined reduction of the mixed layer with entrain of high CO2 subsurface water, damped biological activity and higher surface water temperatures. This study provides the first measurements of atmospheric CO2 flux in these fjord systems and therefore an important new baseline for gaining a better understanding on how the northern Norwegian coast and characteristic fjord systems participate in atmosphere carbon regulation.